2023
DOI: 10.1093/rheumatology/kead292
|View full text |Cite
|
Sign up to set email alerts
|

Damage measured by Damage Index for Antiphospholipid Syndrome (DIAPS) in antiphospholipid antibody-positive patients included in the APS ACTION registry

Abstract: Objectives Our primary objective was to quantify damage burden measured by Damage Index for Antiphospholipid Syndrome (DIAPS) in antiphospholipid antibody (aPL)-positive patients with or without a history of thrombosis in an international cohort. Secondly, we aimed to identify clinical and laboratory characteristics associated with damage in aPL-positive patients. Methods In this cross-sectional study, we analyzed the baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
1
3
2
Order By: Relevance
“…20 In our study, the mean cumulative DIAPS was 1.48 (1.99) (median 0, IQR 0–2; Table 1) which is line with previously reported findings. 5,10,1820 However, it is worth noting that only approximately 48% of our patients presented with damage. This heterogeneity may stem from variations between populations, local patient referencing practices or differences in study methodologies.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…20 In our study, the mean cumulative DIAPS was 1.48 (1.99) (median 0, IQR 0–2; Table 1) which is line with previously reported findings. 5,10,1820 However, it is worth noting that only approximately 48% of our patients presented with damage. This heterogeneity may stem from variations between populations, local patient referencing practices or differences in study methodologies.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies, 8,10,21 our findings indicate that the neuropsychiatric domain is the most affected, followed by the peripheral vascular domain. Contrary reports were found by Torricelli et al 18 and in the APS ACTION cohort, 20 who reported the peripheral vascular domain as the most affected. Overall, these results are consistent with the fact that damage is expected from the main thrombotic manifestations (i.e.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations